Investigation on the relationship between violent death, cocaine abuse and single nucleotide polymorphisms - Pego, Ana Miguel Fonseca (2018)
Violence is a dreadful phenomenon spread throughout the world, resulting in unfortunate events that can ultimately cause death. It is known that some countries play a much worrying role in this scenario than others. Brazil is one of them. The present study has focused on identifying the use of cocaine within 105 postmortem cases arriving at the Institute of Legal Medicine of São Paulo (IML-SP) through analytic toxicological methods and latter applying genetic testing to see whether the presence of certain single nucleotide polymorphisms (SNPs) is more predominant within users rather than non-users, which would help to better understand one\'s susceptibility to abuse the drug. Both blood and hair samples have been analysed through ultra-performance liquid chromatography coupled to electrospray ionization tandem mass spectrometry (UPLC-ESI-MS/MS) in order to distinguish between recent or chronic cocaine use among violent individuals whose violence has ultimately leaded to their death. Two dilute-and-shoot methods have been validated and used for this purpose, and the final residue was analysed through the UPLC-ESIMS/ MS system. From the 105 postmortem cases, a rather high proportion of cocaine and its metabolites was found. A chronic use of the drug was denoted in 53% of the cases, which were positive for cocaine and benzoylecgonine, followed by 43% for norcocaine, 40% for cocaethylene and 13% for anhydroecgonine methyl ester, in hair. As for blood, reflecting the use of cocaine prior to death, 51% of the cases have shown to be positive for benzoylecgonine, followed by 41% for cocaine, 23% for cocaethylene and 20% for norcocaine. These findings suggest a probable association between the use of the drug and risky/violent behaviours. Genetic wise, a significant difference has been observed for SNP rs4263329 from the BCHE gene in its dominant model, with higher frequencies of the genotypes A/G and G/G seen in cocaine users rather than non-users (OR=8.91; 95%CI=1.58-50.21; ρ=0.01). Likewise, also SNP rs6280 from the DRD3> gene presented a significant association in both its additive and dominant model, suggesting that the C allele may be playing a role in cocaine use as both genotypes T/C and C/C were significantly more frequent in users than non-users. This association was not lost when adjusted for covariants using logistic regression (OR=4.96; 95%CI=1.07; ρ=0.04). Finally, a statistically significant association (ρ = 0.003) was also encountered among individuals with both A/G and G/G genotypes within SNP rs4263329 and the use of cocaine HCl (f(A/G+G/G)=44.7%) versus crack-cocaine (f(A/G+G/G)=7.7%) and nonusers (f(A/G+G/G)=16.2%). In conclusion, this study has found significant associations within two SNPs related to cocaine use, however, due to several inherent limitations, these must be confirmed by further studies with a higher number of subjects and within a more controlled setting. Definite assumptions may not be made at this point and future researches are to be conducted.